Potent antibody lineage against malaria transmission elicited by human vaccination with Pfs25 - Brandon McLeod (Nature Portfolio, 2019)
Pfs25 is a transmission-blocking vaccine candidate for Plasmodium. Here, McLeod et al. analyze the antibody response to Pfs25 in sera from a clinical trial evaluating a Pfs25 vaccine candidate, identify a potent transmission-blocking antibody and determine recognized epitopes on Pfs25.